Good Corporate Governance as A Moderating Variable Of The Influence Of Slack Resources on Company Performance - Ade Sandra Dewi; Sri Wahyuni Nur; Septi Wifasari; Petrus Valentino Baunsele; Hamdiah (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
This research is a quantitative study with an explanatory approach, namely an approach that creates new novelty with old reference materials. The data used in this study is primary data that the researcher obtained from private company managers spread throughout Indonesia, totaling one hundred and seventy-five managers. The data that the researcher obtained was analyzed using the smart PLS 4.0 analysis tool. The results in this article show that all hypotheses can be accepted and proven. In the first hypothesis, the results can be seen from the first row of the third table above, where the P-values point to positive and are below the 0.05 significance level, namely 0.008. These results align with research [18], which shows the same results, namely that Slack Resources can have a positive relationship direction and a significant influence on Company Performance. In addition, the Good Corporate Governance variable can also moderate the influence of the Slack Resource variable on Company Performance because the P-values point to positive and are below the 0.05 significance level, namely 0.000. Thus, it can be concluded that this article's first and second hypotheses can be accepted and proven.